2022
DOI: 10.1002/ird.2752
|View full text |Cite
|
Sign up to set email alerts
|

Determining the dynamic responses of cotton root morphological characteristics under waterlogging stress using the minirhizotron technique

Abstract: Roots are important in plant adaption to waterlogging stress. Zero-day (control), 8-day (moderate) and 14-day waterlogging (heavy) stresses were applied on lysimeter-grown cotton plants at flowering. The dynamics of total root length, root surface area, root volume and root number were traced using the minirhizotron technique. The results showed that the rapid root morphological growth period of non-stressed cotton occurred from the early squaring stage to the mid-late flowering stage. The two waterlogging tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Wang et al 5 found that under waterlogging stress, the content of soluble protein and MDA in cotton leaves significantly increased. The waterlogging treatment has a significant promoting effect on the morphological growth of cotton roots, but it only has a promoting effect more than 23 days after the waterlogging ends 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al 5 found that under waterlogging stress, the content of soluble protein and MDA in cotton leaves significantly increased. The waterlogging treatment has a significant promoting effect on the morphological growth of cotton roots, but it only has a promoting effect more than 23 days after the waterlogging ends 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Kong et al 6 found that the root system diameter of hydroponically grown spider plant ( Chlorophytumcomosum ) was smaller than that of soil grown plants. The hydroponic roots contain much fewer crystalliferous cells and amyloplasts in the root cap compared to xeric plants, fewer cortical cells and crystalliferous cells in the mature root regions, and thicker endothelial layers and a smaller pith area in the stele.…”
Section: Introductionmentioning
confidence: 99%